The Güegüence: Identity and Criticism - Mora Fernández, Gabriel (2023)
From the paradigm of cultural studies and in the light of Hall’s, Restrepo’s and Larraín’s theories of identity, as well as Foucault’s discursive formation, an analysis is carried out on different positions on the concept of identity that Nicaraguan literary criticism formulated from Güegüence. Emphasis is placed on literary criticism of the second half of the twentieth century and the cultural-ideological debates established by contemporary literary criticism. It is shown how the notion of identity has gone from arbitrariness to theorization.